2013
DOI: 10.4236/jbise.2013.65a004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hearing in middle-aged patients with diabetes mellitus type 2

Abstract: Introduction: Involvement of auditory pathway is one of the examples of central neuropathy in diabetics. The purpose of this study is to compare the auditory function of patients with type 2 diabetes mellitus with healthy subjects. Methodology: 30 diabetic and 30 healthy subjects participated in this study. For all participants conventional pure-tone audiometry (PTA) and Auditory Brainstem Evoked Responses (ABER) study were performed. Results: In PTA Hearing threshold only at 2, 4, 8 KHz frequencies were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The inter peak latencies were significantly delayed in left ear along with a significant delay of IPL III-V in right ear. So our study correlates with study of Durmus et al, Alam et al, Sharma et al and Forogh et al 9,11,13,14 The prolongation of wave I, is inconsistent feature in the literature as a few authors like Fawi et al and Talebi et al had shown no meaningful difference between diabetics and non diabetics. 10,15 Wave I, produced by acoustic nerve activity (index of peripheral transmission time) and the IPL I-V or central transmission time i.e., considered as most reliable index of brainstem function were significantly impaired in diabetic patients as compared to controls in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The inter peak latencies were significantly delayed in left ear along with a significant delay of IPL III-V in right ear. So our study correlates with study of Durmus et al, Alam et al, Sharma et al and Forogh et al 9,11,13,14 The prolongation of wave I, is inconsistent feature in the literature as a few authors like Fawi et al and Talebi et al had shown no meaningful difference between diabetics and non diabetics. 10,15 Wave I, produced by acoustic nerve activity (index of peripheral transmission time) and the IPL I-V or central transmission time i.e., considered as most reliable index of brainstem function were significantly impaired in diabetic patients as compared to controls in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Prolonged IPL I-III, III-V and I-V explains retro cochlear and brainstem involvement. 14,16,17 It is noteworthy that comparison of ABR prolongation in two types of DM has not achieved much attention in previous studies. Durmus et al found statistically significant difference between latency of wave III and wave V (p<0.05) in two types of diabetes and no significant difference between inter peak latencies in their study.…”
Section: Discussionmentioning
confidence: 99%
“…So far researches carried out to find a causal relationship between diabetes and hearing function, have failed to bring adequate consensus on this matter. A positive correlation between diabetes and hearing loss has been demonstrated by some studies ( Kurien et al., 1989 , Ferrer et al., 1991 , Mitchell et al., 2009 , Diniz and Guida, 2009 , Bainbridge et al., 2010 , Jang et al., 2011 , Forogh et al., 2013 ); however, others failed to find this correlation ( Sieger et al., 1983 , Dalton et al., 1998 , de Espana et al., 1995 ). Analysis of the audiometric data revealed that hearing thresholds of the subjects with elevated FBG were significantly different from the controls at all the frequencies tested ( Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Diabetic subjects were divided into two subgroups ( Table 2 ): diabetes for ≤ 10 years and diabetes for >10 years according to earlier reports ( Forogh et al., 2013 ). The average auditory thresholds of the subjects having diabetes for ≤10 years were 7.82 ± 0.84, 13.47 ± 1.39, 34.67 ± 2.63 and 65.00 ± 3.87 dB at 1, 4, 8 and 12 kHz, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation